Implementation Social Marketing Communication To Promote Anti Violence Of Children - Meilani Dhamayanti, Meilani Dhamayanti (2015)
Violence of children is increasing and must have concern from all people. Every day cases of violence children occured in all region. The cases of violence children such as sexuality harassment, violence on household by parents or nearest people and many another case of violence. Goverment as institution is responsible to take care their citizens already make many effort. Goverment has many agency for overcome violence to children. But, whatever overcome violence to the children not enough just do by the goverment. To solve case of violence children need collaboration between government and other organization and public. In Indonesia, there are many NGO (Non Government Organization) concerned with violence of child. The activity NGO ussually do campaign to promote anti violence of children and advocate cases of child abuse. One of NGO concerned with child violence is HARA Parenting. As Social organization use social marketing communication to campaign anti violence child and advocate cases of violence children.